Overexploitation of Philodendron spiritus-sancti G.S.Bunting and the need to implement a policy for the conservation of “imbés” - Calazans, Luana S. B. (2024)
We present an opinion article contextualizing the current situation of Philodendron spiritus-sancti, an emblematic and endangered species of Araceae, endemic to the Brazilian state of Espírito Santo and highly targeted in the ornamental plant trade. We discuss how the distance between researchers and the civil society difficults the aquisition of information about the species and, consequently, its conservation. Furthermore, we briefly present some considerations to implement a conservation policy for the group.